Effects of Dietary Folate Intake on Migraine Disability and Frequency. Issue 2 (19th January 2015) - Menon, Saras; Lea, Rodney A.; Ingle, Sarah; Sutherland, Michelle; Wee, Shirley; Haupt, Larisa M.; Palmer, Michelle; Griffiths, Lyn R.
<x xml:space="preserve">Abstract</x> Background Migraine is a highly disabling disease affecting a significant proportion of the Australian population. The methylenetetrahydrofolate reductase (MTHFR) C677T variant has been associated with increased levels of homocysteine and risk of migraine with aura (MA). Folic acid (FA), vitamin B6, and B12 supplementation has been previously shown to reduce increased levels of homocysteine and decrease migraine symptoms. However, the influence of dietary folate intake on migraine has been unclear. The aim of the current study was to analyze the association of dietary folate intake in the form of dietary folate equivalent, FA, and total food folate (TFF) on migraine frequency, severity, and disability. Methods A cohort of 141 adult females of Caucasian descent with MA was genotyped for the MTHFR C677T variant using restriction enzyme digestion. Dietary folate information was collected from all participants and analyzed using the "FoodWorks" 2009 package. Folate consumption was compared with migraine frequency, severity, and disability using linear regression. Results A significant inverse relation was observed between dietary folate equivalent (R2 = 0.201, B = −0.002, P = .045, 95% confidence interval [CI] [−0.004, −0.001]) and FA (R2 = 0.255, B = −0.005, P = .036, 95% CI [−0.009, −0.002]) consumption and migraine frequency. It was also observed that in individuals with the CC genotype for the MTHFR C677T variant, migraine frequency was significantly linked to FA consumption (R2 = 0.106, B = −0.004, P = .029, 95% CI [−0.007, −0.004]). Conclusions The results from this study indicate that folate intake in the form of FA may influence migraine frequency in female MA sufferers.